Influencia de habilidades sociales en la comunicación asertiva en alumnos de 5° de secundaria de la I.E. Simón Bolívar, Trujillo 2021 - Sirlupu Quispe, Jahaira Kassandra (2023)
The objective of the research study was to determine how social skills influence the assertive communication of students in the 5th year of secondary school at the I.E. Simón Bolívar, Trujillo 2021. Methods were used for an optimal scope: descriptive-inductive, analytical-synthetic, being basic of the correlational type; techniques such as observation, survey, interview and measurement instruments; presenting a population of 28 students, adolescents, which allowed obtaining the necessary data to analyze the relationship of the variables: Obtaining for the variable social skills, with its dimensions: the existence of coexistence reflects 82%, 64% they affirm the existence of group cohesion, 86% in relation to participation activities and 82% in reference to it; and in turn in assertive communication: With 54% reflecting the existence of communication skills, 57% manage assertiveness in active listening and 46% reflect the existence of negotiation for conflict resolution. In conclusion, in the investigation it was verified that social skills directly influence assertive communication, reflecting in the positive interpersonal relationships and adequate teamwork that the students of 5th year of secondary school of the I.E: Simón Bolívar - Trujillo 2021, Thus, the proposed hypothesis is verified, supported and the existing correlation between both variables is confirmed.